Marangoni migration of a mini bubble in a liquid - Seow, Adele Rae Zhi Ting. (2012)
When a bubble is formed in a temperature field, the surface tension effect is significant on the movement of the bubble. The phenomenon is important in the micro- or nano- scale manufacturing or in space activities. The present project is a study of the effects on the transport driven bubble by the temperature gradient which is known as the Marangoni effect.